Effect of glycine and alanine supplementation on development of cattle embryos cultured in CRlaa medium with or without cumulus cells - Bredbacka, Kristiina; Bredbacka, Peter (Agricultural and Food Science, 1996)
The effect of alanine (1 mM) and glycine (10 mM) supplementation on bovine embryo development in vitro was investigated. Presumptive bovine zygotes, produced by in vitro maturation and insemination of oocytes, were cultured for 144 h in CRlaa medium in the absence (Experiments 1 and 2) or presence of cumulus cells (Experiment 3). In Experiment I, the proportion of morulae and blastocysts of cleaved embryos in glycine-supplemented medium was not different from that of the control medium (34% in both media); however, the cell numbers of morulae and blastocysts were significantly higher in the glycine-enriched medium (69.5 vs. 53.3, P = 0.016). In Experiment 2, addition of alanine did not improve the formation of morulae and blastocysts (13% vs. 21% in control medium), and the mean cell numbers in morulae and blastocysts were lower than those in the control group (34.3 vs. 68.7, P = 0.007). In the presence of cumulus cells, the combined supplementation of glycine and alanine increased the proportion of morulae and blastocysts over that in the control medium (31% vs. 14%, P = 0.003).